Genome-wide analysis of plant glutaredoxin systems - Rouhier, Nicolas (Journal of experimental botany, 2006)
The recent release of the first tree genome (Populus trichocarpa) has allowed a comparison to be made of the multigenic glutaredoxin (Grx) and glutathione reductase (GR) families of this tree with those of other sequenced organisms and especially of the two other fully sequenced plant species, Arabidopsis thaliana and Oryza sativa. Grxs are small proteins involved in disulphide bridge or protein-glutathione adduct reduction, and they are maintained in a reduced form using glutathione and an NADPH-dependent GR. While the P. trichocarpa and O. sativa genomes are nearly five times larger than that of A. thaliana, they contain approximately 45 000 and 37 500 genes compared with the 25 500 genes of A. thaliana. On the one hand, the GR gene composition varies little between species and the gene structures are relatively conserved. On the other hand, the Grx gene family can be divided into three subgroups and the gene content is larger in P. trichocarpa (36 genes) compared with A. thaliana and O. sativa (31 and 27 genes, respectively). This could be partly explained by the occurrence of more duplication events, and this is especially true for one of the three identified Grx subgroups (subgroup III). The expression of most of these genes was confirmed by analysing expressed sequence tags present in various databases. In addition, the expression of Grx of subgroups I and II was examined by RT-PCR in various poplar organs. A complete classification based essentially on gene structure and sequence identity is proposed